Learning about Student Research Practices through an Ethnographic Investigation: Insights into Contact with Librarians and Use of Library Space - Tewell, Eamon; Mullins, Kimberly; Tomlin, Natalia; Dent, Valeda (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2017)
Objective – Student research habits and expectations continue to change, complicating the design of library spaces and the provision of research support. This study’s intent was to explore undergraduate and graduate student research and study needs at a mid-sized university’s two campuses in the Northeastern United States, and to improve librarians’ understandings of these practices so that more appropriate services and spaces may be developed to support student learning.Methods – The research project utilized a primarily qualitative design for data collection that spanned from fall 2012 to summer 2013, consisting of an online questionnaire, unobtrusive observations, and in-depth semi-structured interviews. Data collection commenced with a questionnaire consisting of 51 items, distributed through campus email to all students and receiving 1182 responses. Second, 32 hours of unobtrusive observations were carried out by librarians, who took ethnographic “field notes” in a variety of Library locations during different times and days of the week. The final method was in-depth interviews conducted with 30 undergraduate and graduate students. The qualitative data were analyzed through the application of a codebook consisting of 459 codes, developed by a data analysis team of 4 librarians.Results – The results address topical areas of student interactions with librarians, contact preferences, and use of library space. Of the interviewees, 60% contacted a librarian at least once, with texting being the most popular method of contact (27%). In being contacted by the library, students preferred a range of methods and generally indicated interest in learning about library news and events through posters and signage. Participants were less interested in receiving library contact via social media, such as Facebook or Twitter. Regarding student use of and preference for library space, prominent themes were students creating their own spaces for individual study by moving furniture, leaving personal items unattended, the presence of unwanted noise, and a general preference for either working nearby other students in groups or in carrels to facilitate individual study.Conclusions – Being aware of student research processes and preferences can result in the ability to design learning environments and research services that are more responsive to their needs. Ethnographic research methods, as part of an ongoing research process, are recommended as a means to better understand library user practices and expectations.